THE EFFECT OF FIRM SIZE, SALES GROWTH, AND PROFITABILITY ON FIRM VALUE IN HEALTHCARE, TECHNOLOGY, AND FOOD AND BEVERAGE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2020 PERIOD - Mutiara, Nanda; Purwohedi, Unggul; Zulaihati, Sri (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study uses empirical evidence to confirm the impact of firm size, sales growth, and profitability on firm value. The research approach employed is quantitative. This research uses secondary data from the 2017-2020 financial statements of Healthcare, Technology, and Food and Beverage companies listed on the Indonesia Stock Exchange. Using the purposive sampling method, 37 samples were collected from the population of 120 firms comprising the study. A multiple linear regression analysis will be undertaken using version 25 of the Statistical Package for the Social Sciences (SPSS) to test the hypothesis. Results suggested that company size and sales growth did not influence firm value, but profitability did.